Development of clinical guidelines for pre and post-anaesthetic assessment in Ghana - Tenkorang-Twum, David (My University, 2022)
Background: Clinical guidelines are evidence-based tools designed to help clinicians provide safe and consistent clinical care. Due to the wide range of contexts in which anaesthesia is practised, existing clinical guidelines are challenging to execute in Ghana. Purpose: To develop clinical guidelines that may inform pre- and post-anaesthetic assessment of surgical clients to improve surgical safety and post-operative outcomes. Methodology: In four phases, the researcher recruited certified registered anaesthetists and physician anaesthetists in Ghana. The study utilized an explanatory sequential mixed method design: quantitative, qualitative, integrative review, and document analysis. The AGREE II instrument was used to inform the clinical guidelines development. Results: Phase I: Early detection and intervention of complications, fluid, and effective pain management are key strategies for excellent recovery and patient comfort. Phase II: Post- anaesthetic assessment has been poor at all four levels of care, with time constraints and early discharge cited as primary causes of unsatisfactory practice. Phase III: Anaesthetic assessment is vital and could improve practice and patient safety, but it is challenged by inadequate logistics and healthcare financing and a shortage of staff. Phase IV: Anaesthetic document analysis exposed patients’ biographical information that may help in recognizing patients' problems, such as comorbidities, which may have a negative impact on surgical decisions and anaesthesia administration. Conclusion: Ghanaian anaesthetists may be trained to use the developed pre and postanaesthetic assessment guidelines. Well-staffed post-anaesthesia care units (PACU) with regular follow-up visits are essential for patient safety. These recommendations may be useful for anaesthesia teaching, practice, and research.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022